Intervention for Women in Costa Rica Who Have Food Insecurity and Excess Body Weight: A Cluster Randomized Trial (P04-017-19). (13th June 2019) - Martínez-Jaikel, Tatiana; Frongillo, Edward; Blake, Christine; Fram, Maryah; Murillo-Castro, Adriana; Esquivel-Solís, Viviana
Abstract: Objectives: This study aimed to develop, implement, and evaluate an intervention to simultaneously reduce food insecurity and body weight. We hypothesized that, when compared with the non-intensive arm, women in the intensive intervention arm would reduce food insecurity and body weight and improve social support for healthy eating, psychological and economic empowerment, and food and physical activity behaviors. Methods: We conducted a cluster-randomized controlled trial in the Central Canton of the Province of Alajuela. Randomization was at the level of the catchment area of the first level of health care in Costa Rica. This 6-month study compared two arms. The intensive arm consisted of activities at the individual (12 two-hour sessions, three follow-up monthly sessions, and one closing session), household (one workshop with the participants' household and community members, and homework with family participation), and community (two brochures and one workshop) levels. The non-intensive arm was comprised of three one-hour sessions about healthy lifestyles. Results: A total of 171 participants were enrolled (83 in intensive and 88 in non-intensive arm). At 6 months the intensive arm had significantly greater decreases from baseline in food insecurity ( P  = 0.004), body mass index ( P  = 0.010), and waist circumference ( P  = 0.001) compared with the non-intensive arm. The intensive arm also had also significantly greater increases in psychological ( P  = 0.014) and economic empowerment, including a greater increase in the contribution to household support ( P  = 0.030) and more women that found a job ( P  = 0.018), compared with the non-intensive arm. Women in the intervention arm had significantly greater changes from baseline in the expected direction in food consumption of fried foods ( P  = 0.029), sausages ( P  = 0.038), sugar drinks ( P  = 0.032), salads ( P  = 0.032), and beans ( P  = 0.004) compared to women in the non-intensive arm. We did not find any significant differences between the arms in social support, exercise, and consumption of fruits, vegetables and fast foods. Conclusions: This intervention demonstrates that it is possible to simultaneously reduce food insecurity and reduce, rather than exacerbate, excess weight gain. Funding Sources: Office of International Affairs, University of Costa Rica.